CATHOLIC DOCTRINES OF ORIGIN OF THE STATE AND LAW - Яртим, Н. В. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
The article is devoted different philosophical-religious to conceptions of origin of the state and law, and also looks, on their setting. The theology theory of origin of the state is specified and specified, looks are examined to the state and right from the side of authors, the looks of founders of contractual theory of origin of the state and right light up – Jesuits of Bellarmina and Suaresa